Perception and Practices of Academic Leadership in Technical Schools (Journal of Training and Development, 2017)
This qualitative case study research explored leaders’ and faculty members’ perspectives on the nature of academic leadership at the technical schools in Kathmandu Valley. The study aimed to gain insights about academic leadership as practiced in a Nepalese technical school. Data for the study was collected from leaders and faculty members of technical schools in Kathmandu Valley through semi-structured interviews which were then analyzed thematically. Following an interpretivist worldview and drawing insights from leadership theories enabled understanding of the academic leadership practices at the technical schools. The study revealed that differences in the perspectives of leaders and faculty members on academic leadership at technical schools are influenced by the leadership knowledge, experience and training of leaders. Further, the study illustrated that understanding of academic leadership is affected by the Nepalese culture.